2015
DOI: 10.17531/ein.2015.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis and prediction for time to failure distribution of an automobile crankshaft

Abstract: Article citation info: Singh SSK, AbdullAh S, MohAMed nAn. Reliability analysis and prediction for time to failure distribution of an automobile crankshaft. eksploatacja i niezawodnosc - Maintenance and Reliability 2015; 17 (3): 408-415, http://dx.doi.org/10.17531/ein.2015.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Reliability is an important tool in lifetime prediction for components especially in the electronic industry [16]. Evaluating the reliability indices such as the MTTF (mean time to failure) and percentile of the cycle life distribution, is an essential task in cycle life prediction for Lithium-ion cells.…”
Section: Life Prediction Ignoring Temperature Effectmentioning
confidence: 99%
“…Reliability is an important tool in lifetime prediction for components especially in the electronic industry [16]. Evaluating the reliability indices such as the MTTF (mean time to failure) and percentile of the cycle life distribution, is an essential task in cycle life prediction for Lithium-ion cells.…”
Section: Life Prediction Ignoring Temperature Effectmentioning
confidence: 99%
“…It is demonstrated that the reliability of a vehicle is very different because of its driving [10]. e reliability of an automobile crankshaft is analyzed and predicted through analyzing the time to failure [11]. A method of estimating automotive component reliability uses field warranty repair data that comprises early failure data [12].…”
Section: Introductionmentioning
confidence: 99%
“…The extremely loaded component of every vehicle is obviously the power unit and its crank-piston assembly components, the gearbox and engine equipment. The source of main loads acting on the assembly are gas and inertia forces arising during combustion of the fuel-air mixture, resulting from masses set in reciprocating or rotary motion (Singh et al, 2015). The nature of these forces is periodic, and their frequency depends directly on the rotational speed of the motor shaft.…”
Section: Introductionmentioning
confidence: 99%